2010
DOI: 10.1118/1.3514123
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐CT dilatometry measures of molecular collagen hydration using bovine extensor tendon

Abstract: Results validate the use of tendon dilatometry amplification factors of 10(6)-10(8) as an effective model to investigate protein molecule shape change response to solvent molecules. The tendon model for the first time allows direct study of protein hydration and functional response under physiological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…Validation studies by Martiniova et al demonstrated that the accuracy of T2-weighted MRI volume measurements was within about 8% [22]. In the present study, unlike the prior studies, in-air micro-CT image volume of excised tumors was calculated as reference tumor volume using the methodology previously shown by Fullerton et al [14]. Using the reference tumor volume, then image-based volumes were quantified and compared among three commonly used imaging modalities (US, micro-CT and MRI) in rodent tumor models.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Validation studies by Martiniova et al demonstrated that the accuracy of T2-weighted MRI volume measurements was within about 8% [22]. In the present study, unlike the prior studies, in-air micro-CT image volume of excised tumors was calculated as reference tumor volume using the methodology previously shown by Fullerton et al [14]. Using the reference tumor volume, then image-based volumes were quantified and compared among three commonly used imaging modalities (US, micro-CT and MRI) in rodent tumor models.…”
Section: Introductionmentioning
confidence: 78%
“…To our knowledge, the accuracy of in-air micro-CT image volume had not previously been validated for tumor studies and it has not been used before as a reference/true tumor volume. Fullerton et al in the same research group initially proved that in-air micro-CT image volume is fairly accurate (~0.6%) [14] and we adopted the method. For this study, we assumed that no dehydration of excised tumors occurred during the time (less than 10 min) between tumor excision and completion of the micro-CT scans.…”
Section: In-air Micro-ct Image Volume As Alternative Gold Standardmentioning
confidence: 99%
See 2 more Smart Citations
“…The viscous thick albumen hen egg white is a hydrogel fraction and can be separated from the thin egg white sol fraction by sieve filtration (Cameron and Fullerton 2010). The shaking of thick albumen gel caused the transition from a gel state to a sol state as demonstrated by flow through the sieve filter.…”
Section: Physical Measured Properties Of Bulk and Non-bulk Water Fracmentioning
confidence: 99%